1998
DOI: 10.1097/00005176-199810000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Preterm Infants: Norms for Extended Distal Esophageal pH Monitoring

Abstract: The norms (reference values) for well, asymptomatic preterm infants were comparable to those seen in term infants, children, adolescents, and adults. With the establishment of these norms, the search for a causal link between many of the respiratory problems encountered in prematurity and gastroesophageal reflux may be aided and the complications associated with gastroesophageal reflux may consequently be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…7 9 10 Vandenplas et al ,5 who studied the largest series of mature infants, showed that the reflux index is not normally distributed in this population 5. Attempting to define the upper limit of normal in preterm infants using mean (SD) is unlikely to be meaningful for this reason.…”
Section: Normal Valuesmentioning
confidence: 89%
“…7 9 10 Vandenplas et al ,5 who studied the largest series of mature infants, showed that the reflux index is not normally distributed in this population 5. Attempting to define the upper limit of normal in preterm infants using mean (SD) is unlikely to be meaningful for this reason.…”
Section: Normal Valuesmentioning
confidence: 89%
“…The problem then comes in trying to interpret how these results have been achieved. In reviewing the world literature for outcome measures in childhood ALL, it is immediately evident that despite considerable efforts made more than 10 y ago at the Rome Consensus Meeting (5), and confirmed once again at an international childhood ALL workshop held at St Jude Research Hospital, Memphis, USA in 1997, that consistent criteria should be used to stratify patients for analysis (6), treatment groups still present data…”
Section: Ob Edenmentioning
confidence: 99%
“…Reference to normal values should help to avoid misinterpretation of the results, keeping in mind that maturation of antireflux function occurs during the first year or so of life. With the recent publication of norms for extended distal oesophageal pH monitoring in preterm infants (6), the whole age range has been covered. Scintigraphy is even more sensitive, so that positive findings can be easily overinterpreted and it should be reserved for research use.…”
mentioning
confidence: 99%
“…Using three‐site pH monitoring, Toohill et al 201 found a higher incidence of abnormal reflux events in patients with laryngotracheal stenosis than in control subjects. Ng and Quak 202 have defined normal values for extended distal esophageal pH monitoring in preterm infants. Two authors discuss the significance of duodenogastric reflux 203 .…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%